أثر المناخ النفسي على التمكين النفسي لدى العاملين في شركات الخدمات الخاصة في مدينة الرياض - Alotaibi, Saad (مجلة العلوم الإدارية و الإقتصادية, 2018)
The current study aimed to examine the relationship between psychological climate and psychological empowerment among private service companies employees in Riyadh, and it has sought to examine the role of Psychological climate in predicting psychological empowerment, the study was conducted on a sample of (422) employees in private service companies in Riyadh, and the results of the study revealed that staff’s perceptions about psychological climate was positive, the results of the study also revealed that employees of private service companies fell a moderate level of psychological empowerment, the study results showed that psychological climate significantly and positively predicted psychological empowerment. Based on the results, the study concluded a series of recommendations that aim to promote psychological climate and employee empowerment.